The Phenomena about the Impact of TKI Migration on Their Children’s Education at Sambelia District of East Lombok Regency, Indonesia - Sari, Reno Yandhora; Afdhal, Afdhal (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This study was aimed to know the impact of the migration of Indonesian worker (referred as TKI) family on children’s education at Sambelia District of East Lombok Regency. This research using qualitative approach. Collecting data technique were observation, interview and documentation. The type of the data are primary and secondary data. Primary data collected by respondent interviews and secondary data collected by state government. To analyze the data, the researcher using qualitative model by Miles and Huberman: data reduction, display data, and conclusion. Other data analysis such as government policy and raw data from state government of East Lombok using AHP Model and statistic analysis. The result found that 40% of children whose parents were TKI suffered from poor psychosocial development in terms of achievement and not having close friend. A long-term impact was that those children might drop out of school and more likely experienced psychological wellbeing disorders like emotional disorder. Children from TKI family who grew and developed with only one of the parents tended to be more disobedient. They tended to skip school and chose to spend time for playing. According to the score of Consistency Ratio, the highest score was obtained by factor of socio-economy (0.373) followed by factor of poor life skill (0.277), factor of not being accepted in the environment (0.205), and factor of higher life necessities (0.146).